Responsabilidade social empresarial do varejo no Brasil: um estudo, multi casos em empresas de grande porte - Terepins, Fanny Michaan (2005)
The purpose of this study is to investigate the performance of Brazilian retail network companies concerning Corporate Social Responsibility (CSR), trying to investigate the stage in which these companies are, and if the geographic capillary retail network characteristics, direct contact with the community, strong link with the clients, interaction between clients and employees and the physical nearness of Non Governmental Organizations and public institutions, are well used. For that intention concepts (ideas/conceits) of administration management were used, such as the engagement of the board, incorporation of CSR values in the management and strategic planning, autonomy and management of CSR in the stores. The management was considered by the sight of the Austin´s Collaboration Continuum, and the practices of CRS by the Stakeholders Theory, using as a fundamental principle the dimensions of the Ethos Social Responsible indicators. Kotler and Lee´s theory, for classifying the initiatives as concepts of marketing was also used. An exploratory survey with five large companies of the retail market was conducted. The results point out that in most of the companies the application of these practices is recent. It is evident that the companies differ in terms of the stage of CRS, and that the retail characteristics are not being well used in the whole. Hypothesis are raised so that they can make good use of the store structure to attend the local community.